2017
DOI: 10.1097/md.0000000000008550
|View full text |Cite
|
Sign up to set email alerts
|

Graves disease following radioiodine therapy for toxic adenoma

Abstract: Rationale:There is a low risk of developing Graves disease (GD) with elevated thyrotropin receptor antibodies (TRAbs) in patients undergoing radioiodine therapy for toxic adenoma.Patient concerns:An old female patient with a history of Hashimoto thyroiditis was referred to our department due to thyrotoxic symptoms. After the administration of radioiodine, a significant remission was achieved. However, after 4 months, she was referred to our department again due to recurrence of hyperthyroid symptoms.Diagnoses:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
3
0
4
Order By: Relevance
“…O adenoma tóxico (AT) é um nódulo tiroideu único, de funcionamento autónomo, responsável pela síntese excessiva e descontrolada de HT independentemente do estímulo da TSH. 10 Mutações somáticas dos genes TSHR (recetor da TSH) e da subunidade proteica G provocam a ativação constitutiva do recetor de TSH e provocam o crescimento do adenoma e a produção descontrolada de HT. 11 No AT, ao contrário do que se passa na DG e em outras causas autoimunes, analiticamente não se verifica a presença de anticorpos (nem TRAb nem TPO) que se liguem ao recetor de TSH na glândula tiroideia.…”
Section: Adenoma Tóxicounclassified
See 3 more Smart Citations
“…O adenoma tóxico (AT) é um nódulo tiroideu único, de funcionamento autónomo, responsável pela síntese excessiva e descontrolada de HT independentemente do estímulo da TSH. 10 Mutações somáticas dos genes TSHR (recetor da TSH) e da subunidade proteica G provocam a ativação constitutiva do recetor de TSH e provocam o crescimento do adenoma e a produção descontrolada de HT. 11 No AT, ao contrário do que se passa na DG e em outras causas autoimunes, analiticamente não se verifica a presença de anticorpos (nem TRAb nem TPO) que se liguem ao recetor de TSH na glândula tiroideia.…”
Section: Adenoma Tóxicounclassified
“…11 No AT, ao contrário do que se passa na DG e em outras causas autoimunes, analiticamente não se verifica a presença de anticorpos (nem TRAb nem TPO) que se liguem ao recetor de TSH na glândula tiroideia. 10…”
Section: Adenoma Tóxicounclassified
See 2 more Smart Citations
“…5,6 Several studies have shown an increase of thyrotropin receptor antibodies after radioiodine treatment then radioiodine-induced Graves disease could be interpreted as an immunization against antigens released during the destruction of thyroid cells. [7][8][9]…”
mentioning
confidence: 99%